Pemanfaatan Sampah Organik Rumah Tangga Menjadi Pupuk Organik Cair (POC) di Desa Jati, Kabupaten Sidoarjo - Tukiman Tukiman; Aldo Nandacatur Aldriansyah; Adinda Tarisa Salsabila; Auliyah Shabirah Supriyono; Nafa Shoimah; Aulya Kineta; Devina Defa Syaharani; Dewi Mardiana Aditya; Awaliya Rahmadhani Syafitra; Gina Nur Maya Jannah; Reihan Rafly Prasetya (Lembaga Pengembangan Kinerja Dosen, 2024)
This activity aims to utilize household organic waste into liquid organic fertilizer (POC) in Jati Village, Sidoarjo Regency. Organic waste that generally comes from leftover food and vegetables is often just thrown away and causes an unpleasant odor and environmental pollution. Through counseling and practice of making POC, the community is expected to be able to process organic waste into fertilizer that is beneficial for plants. The method used involves counseling on the importance of processing organic waste, as well as practical steps in making POC, including preparation of materials, cutting, mixing with supporting materials such as brown sugar and EM4, fermentation process, filtering, and storage. The results of the activity show that the community has become more aware of the importance of processing organic waste and can practice making POC independently in their respective homes. This program not only reduces the amount of waste disposed of to landfills (TPA) but also increases soil fertility and contributes to environmental sustainability